2003
DOI: 10.1523/jneurosci.23-09-03566.2003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Neurotrophins on Synaptic Protein Expression in the Visual Cortex of Dark-Reared Rats

Abstract: Total lack of visual experience [dark rearing (DR)] is known to prolong the critical period and delay development of sensory functions in mammalian visual cortex. Recent results show that neurotrophins (NTs) counteract the effects of DR on functional properties of visual cortical cells and exert a strong control on critical period duration. NTs are known to modulate the development and synaptic efficacy of neurotransmitter systems that are affected by DR. However, it is still unknown whether the actions of NTs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
96
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(104 citation statements)
references
References 44 publications
(52 reference statements)
7
96
0
Order By: Relevance
“…4 Structure-activity studies revealed that peptides containing the highly hydrophobic 25-35 region formed stable aggregates and mediated neuronal death by necrosis or apoptosis. 5,6,7 The truncated A␤ [25][26][27][28][29][30][31][32][33][34][35] fragment includes extracellular and intramembrane residues that have been reported to represent an active region of A␤. 8 In vivo, two nontransgenic rodent models of AD have been studied to analyze the molecular, morphological, and behavioral consequences of amyloid toxicity: the infusion of A␤ 1-40/42 protein and the injection of preaggregated A␤ [25][26][27][28][29][30][31][32][33][34][35] peptide.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…4 Structure-activity studies revealed that peptides containing the highly hydrophobic 25-35 region formed stable aggregates and mediated neuronal death by necrosis or apoptosis. 5,6,7 The truncated A␤ [25][26][27][28][29][30][31][32][33][34][35] fragment includes extracellular and intramembrane residues that have been reported to represent an active region of A␤. 8 In vivo, two nontransgenic rodent models of AD have been studied to analyze the molecular, morphological, and behavioral consequences of amyloid toxicity: the infusion of A␤ 1-40/42 protein and the injection of preaggregated A␤ [25][26][27][28][29][30][31][32][33][34][35] peptide.…”
mentioning
confidence: 99%
“…These models have led to highly pertinent pathomimetic observations and provide complementary approaches to the numerous transgenic mouse lines developed as AD models. In particular, at 1 week after A␤ [25][26][27][28][29][30][31][32][33][34][35] injection, reactive gliosis was observed in the rat hippocampus, 9 caspase-3 activity was induced in the hippocampus and cortex, 9 a reduction in the number of neurons was measured in the CA1 or CA3 hippocampal area, 9 -11 and significant oxidative stress was observed. [11][12][13] Nonetheless, this amyloid toxicity model remains controversial with respect to AD.…”
mentioning
confidence: 99%
See 3 more Smart Citations